Synovial Macrophages: Past Life, Current Situation, and Application in Inflammatory Arthritis - Bai, Lin-Kun; Su, Ya-Zhen; Wang, Xue-Xue; Bai, Bing; Zhang, Cheng-Qiang; Zhang, Li-Yun; Zhang, Gai-Lian (Frontiers in Immunology, 2022)
Inflammatory arthritis is an inflammatory disease that involves the joints and surrounding tissues. Synovial hyperplasia often presents when joints become inflamed due to immune cell infiltration. Synovial membrane is an important as well as a highly specific component of the joint, and its lesions can lead to degeneration of the joint surface, causing pain and joint disability or affecting the patients’ quality of life in severe cases. Synovial macrophages (SMs) are one of the cellular components of the synovial membrane, which not only retain the function of macrophages to engulf foreign bodies in the joint cavity, but also interact with synovial fibroblasts (SFs), T cells, B cells, and other inflammatory cells to promote the production of a variety of pro-inflammatory cytokines and chemokines, such as TNF-α, IL-1β, IL-8, and IL-6, which are involved in the pathogenic process of inflammatory arthritis. SMs from different tissue sources have differently differentiated potentials and functional expressions. This article provides a summary on studies pertaining to SMs in inflammatory arthritis, and explores their role in its treatment, in order to highlight novel treatment modalities for the disease.